Isolation and characterization of a novel mycobacteriophage Kashi-VT1 infecting Mycobacterium species - Nayak, Tanmayee; Kakkar, Anuja; Singh, Rakesh Kumar; Jaiswal, Lav Kumar; Singh, Anand Kumar; Temple, Louise; Gupta, Ankush (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacteriophages are viruses that infect members of genus Mycobacterium. Due to the rise in antibiotic resistance in mycobacterial diseases such as tuberculosis, mycobacteriophages have received renewed attention as alternative therapeutic agents. Mycobacteriophages are highly diverse, and based upon their genome sequences, they are grouped into 30 clusters and 10 singletons. In this article, we have described isolation and characterisation of a novel mycobacteriophage Kashi-VT1 (KVT1) infecting Mycobacterium smegmatis mc2155 (MsmegM. smegmatis) and M. fortuitum isolated from Varanasi, India. KVT1 is a cluster K1 temperate phage that belongs to Siphoviridae family as visualised in transmission electron microscopy. The phage genome is 61,010 bp with 66.5% GC content, encoding 101 putative open reading frames. The KVT1 genome encodes an immunity repressor, tyrosine integrase and excise protein, characteristic of temperate phages. It also contains genes encoding holin, lysin A and B involved in host cell lysis. The one step growth curve demonstrated that KVT1 has a latency time of 90 minutes and an average burst size of 101 phage particles per infected cell. It can withstand a temperature up to 45ºC and has maximum viability between pH 8 and 9. Some Mycobacteriophages from cluster K are known to infect the pathogenic Mycobacterium tuberculosis (MtbM. tuberculosis); hence, KVT1 holds potential for the phage therapy against tuberculosis, and it can also be engineered to convert into an exclusively lytic phage.